2017
DOI: 10.1049/mnl.2016.0374
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced visible photocatalytic activity in flower‐like CuO–WO 3 –Bi 2 WO 6 ternary hybrid through the cascadal electron transfer

Abstract: The flower‐like CuO–WO3–Bi2WO6 with p–n–n heterostructure was prepared via a simple two‐step approach, which was using hydrothermal method synthesising WO3–Bi2WO6 and subsequent CuO recombination through impregnation‐calcination technique. The products were characterised by X‐ray powder diffraction, energy dispersion spectroscopy, scanning electronic microscopy, transmission electron microscopy, nitrogen sorption measurements (BET), UV–vis diffuse reflectance spectra, photoluminescence (PL) emission spectra, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…16,26–46 The n-type semiconductor Bi 2 WO 6 is an ideal selection for constructing a heterojunction with WO 3 , due to its unique layered structures composed of corner-shared WO 6 octahedral layers and [Bi 2 O 2 ] 2+ layers. 47–58 Once Bi 2 WO 6 and WO 3 form a 2D/2D heterojunction, a superior coupling interface will be formed, which accelerates the charge migration at the interface. The strong reducing ability of Bi 2 WO 6 due to photo-generated electrons and oxidizing ability of WO 3 due to photo-generated holes can be fully utilized due to the suitable band positions, which is of great significance in enhancing the catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…16,26–46 The n-type semiconductor Bi 2 WO 6 is an ideal selection for constructing a heterojunction with WO 3 , due to its unique layered structures composed of corner-shared WO 6 octahedral layers and [Bi 2 O 2 ] 2+ layers. 47–58 Once Bi 2 WO 6 and WO 3 form a 2D/2D heterojunction, a superior coupling interface will be formed, which accelerates the charge migration at the interface. The strong reducing ability of Bi 2 WO 6 due to photo-generated electrons and oxidizing ability of WO 3 due to photo-generated holes can be fully utilized due to the suitable band positions, which is of great significance in enhancing the catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the photocatalytic activity of the BTO/CTO-X nanocomposites after loading with Bi, Bi-BTO/CTO-15 and Bi-BTO/CTO-100 showed a slight decrease in activity compared to the pure BTO/CTO samples, and the NO removal rates of Bi-BTO/CTO-25 and Bi-BTO/CTO-50 samples increased to 52.06% and 64%, respectively, (Figure 5a) which were higher than those of the individual BTO/CTO. Among the composite photocatalysts, Bi-BTO/CTO-50 (64%) showed the most superior photocatalytic performance even exceeding other types of sim- Electrochemical impedance spectroscopy (EIS) measurements were used to gain insight into the behavior of photo-induced h + -e − pairs in BTO/CTO and Bi-BTO/CTO-X photocatalysis [27,28]. The results in Figure 4c show that (1) all samples have only one arc in the AC impedance spectral plane, indicating that the photocatalytic reaction involves only surface charge transfer; and (2) the sample Bi-BTO/CTO-50 has the smallest arc radius on the AC impedance Nyquist diagram.…”
Section: Photocatalytic Performance Of No Removalmentioning
confidence: 99%
“…However, the rapid recombination of photogenerated charges and the narrow light absorption range limit its photocatalytic activity. Further improvements to the photocatalytic efficiency can be achieved by using doping ions [11], supporting semiconductors [12][13][14], metal organic framework coupling [15] and precious metal deposition [16][17][18]. Although doping precious metals or ions can improve the separation efficiency of photogenerated electrons and holes by trapping electrons or structural defects, precious metals and ions may also become the recombination centers of electrons and holes which reduces the photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported that the three-dimensional structure of CuO-WO 3 -Bi 2 WO 6 degraded 95% of Rhb within 100 min. The enhanced photocatalytic activity can be attributed to the p-n-n type heterojunction, which transfers electrons from CuO to Bi 2 WO 6 and then transfers to WO 3 through the interface potential gradient in the ternary hybrid conduction band, thereby improving the photogenerated carriers separation rate [12]. Meng et al synthesized CuO/Bi 2 WO 6 that effectively improved the light absorption capacity and had good photocatalytic stability [33].…”
Section: Introductionmentioning
confidence: 99%